V.2 - "Menon , Ganesh .C. (ed.)" (New Delhi, 2009)
This work emphasizes Human Rights NGOs, which have been traditionally separated from relief, humanitarian assistance, and development-oriented NGOs. A set of three volumes offer important observations about the significant roles NGOs have played in promoting and protecting human rights.
Keywords: NGOs; Human Rights